Infected by art. Volume 5 - Spoor, Todd; Cox, Bill (Comic book artist) (b, 2017)
This ground-breaking edition features over 300 pieces of art from the world's finest fantasy, science fiction, and horror artists in a range of media. Infected by Art hosts an annual art competition where a jury of artists and art directors choose the works that make it into each Volume. Grand Prize winners in IBA 5 include Vanessa Lemen, David Palumbo, Matt Smith, Vince Natale and Travis Lewis. This Volume's Body of Work award winner was artist Allen Williams.
Compilation of artwork from the Infected by Art website online competition.
Keywords: Fantasy in art -- Pictorial works; Science fiction in art -- Pictorial works